The Problems of Detection and Registration of Infections Specific to the Perinatal Period in Neonates - M. D. Zlokazov; A. V. Liubimova; I. G. Tekhova; N. M. Khrustaleva; L. A. Ivanova; А. A. Zlokazova; I. S. Bazaeva; T. V. Os`mirko; A. G. Komissarov; V. V. Nechaev (Эпидемиология и вакцинопрофилактика, 2018)
Objective. The frequency of diagnosing intrauterine infections is increasing every year. assessment of the frequency of intra-amniotic infection of the fetus using the standard case definition.Subject and methods: a study, conducted in one of the maternity hospitals of St. Petersburg, included 110 newborn children with an established diagnosis of intra-amniotic infection. To clarify the diagnosis, we have applied the probable and confirmed standard definitions of the case.Results: a study showed that the diagnosis of intraamniotic infection was consistent with the standard case definition in 30.9% of cases.Conclusion:  the introduction of standard case definitions will make it possible to unify the registration and notification of the intrauterine infections by different specialists in all types of healthcare settings and will allow a unified approach to identification of the intrauterine infections, both in maternity hospitals and in the neonatal units of children's hospitals.